2001
DOI: 10.2136/sssaj2001.653853x
|View full text |Cite
|
Sign up to set email alerts
|

Residue Cover and Surface‐Sealing Effects on Infiltration

Abstract: may decrease infiltration (Savabi and Stott, 1994) and is an issue we do not consider in this study. Surface sealing of bare soils often reduces rain infiltration, and The relationship between the mass or extent of resicrop-residue cover is commonly used to reduce surface sealing. We due cover and the increase in infiltration is an important conducted numerical experiments to quantify effects of the percentage and distribution of residue cover on infiltration, and to provide guide-issue in dealing with the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 20 publications
3
29
0
2
Order By: Relevance
“…Introducing sealing in catchment-scale models is additionally hindered by the large spatial heterogeneity of seal development resulting from small-scale differences in soil properties, soil cover (e.g. Ruan et al, 2001), microtopography, management, etc. Nevertheless, some applications of hydrological or erosion models have successfully integrated sealing processes as one of the key drivers of surface runoff (e.g.…”
Section: Soil Sealingmentioning
confidence: 99%
“…Introducing sealing in catchment-scale models is additionally hindered by the large spatial heterogeneity of seal development resulting from small-scale differences in soil properties, soil cover (e.g. Ruan et al, 2001), microtopography, management, etc. Nevertheless, some applications of hydrological or erosion models have successfully integrated sealing processes as one of the key drivers of surface runoff (e.g.…”
Section: Soil Sealingmentioning
confidence: 99%
“…Substantial rainfall (about 86-94%) infiltrated into the soil, and the three double cropping systems increased the infiltration by 4-10% compared with the wheat/fallow system. Surface crop cover has been reported to intercept the rainfall and protect the soil surface from raindrop impact, increasing the infiltration around crop roots, thus reducing surface runoff (Castillo et al 1997;Catt et al 1998;Ruan et al 2001). Gao et al (2009) found that the growth of vegetation shoots and roots improved soil physical properties around roots and prevented surface soil sealing, thus increasing the infiltration rate.…”
Section: Resultsmentioning
confidence: 99%
“…Surface runoff and soil erosion are effectively reduced by increasing ground crop cover (Bochet et al 2006;Ruan et al 2001). Cover crops and crop residue cover are common best management practices (BMPs) that decrease surface runoff and soil erosion, thus minimizing P loss from agriculture fields (Barnett et al 1972;Catt et al 1998;Grande et al 2005;Sharpley and Smith 1991;Torbert et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in runoff on raised beds under minimum or no tillage has been reported before for other soils (Boulal et al, 2008;Jordán et al, 2010;Verhulst et al, 2011;Zhang et al, 2007), as well as reduction of soil loss under permanent beds (Oicha et al, 2010). Reduction of soil loss was attributed to increased soil macro-porosity associated with greater macro-fauna activity (Kay and Vanden Bygaart, 2002;Ruan et al, 2001;Trojan and Linden, 1998), reduced soil surface sealing (Mannering and Meyer, 1963), and increased soil surface roughness through the presence of crop residues, which enhance flow path tortuosity slowing down the water flow rate across the soil surface (Findeling et al, 2003). Actual runoff is the result of a multiplicity of factors, the interaction of which is poorly understood.…”
Section: Runoff and Erosionmentioning
confidence: 61%